Development of a floxed Gabbr2 gene allows for widespread conditional disruption of GABBR2 and recapitulates the phenotype of germline Gabbr2 knockout mice - Julie Rose Hens; Stacey Brown; Pawel Licznerski; Jacqueline Suarez; Elizabeth Jonas; John J. Wysolmerski (PLoS ONE, 2025)
GABBR1 and GABBR2 are widely expressed in the brain and genetic inhibition of their function leads to neurologic dysfunction and premature death in mice. Given that GABBR1 and GABBR2 heterodimerize to form a functional receptor, global knockout of GABBR1 or GABBR2 results in a similar phenotype, characterized by spontaneous epileptiform activity, hyperlocomotor activity, hyperalgesia, impaired memory and premature death. Both GABBR1 and GABBR2 are expressed in a variety of tissues outside the nervous system and GABA-B receptors have been shown to heterodimerize with other class C GPCRs. However, the neurologic consequences of global GABBR1 or GABBR2 knockout mice have made it difficult to study the effects of loss of GABBR function in other organs. While a conditional knockout for GABBR1 is available, the Gabbr2 gene had not been “floxed”. Therefore, we used CRISPR to insert loxP sites into the Gabbr2 locus in mice. These mice are normal at baseline but when bred with mice expressing Cre-recombinase under the control of the ubiquitously expressed Actin gene promoter, Gabbr2 lox/lox mice recapitulate the phenotype of global GABBR2 knockout mice demonstrating alterations throughout the brain, including the cortex, hippocampus and cerebellum. We document abnormal neurological function, increased neuronal cell death, changes in neuronal architecture, and premature death. These mice should be useful tools to study cell type-specific loss of GABBR2 function in the brain and other organs.